2021
DOI: 10.3171/case2197
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making for decompressive craniectomy in traumatic brain injury aided by multimodality monitoring: illustrative case

Abstract: BACKGROUND Severe traumatic brain injury (TBI) requires individualized, physiology-based management to avoid secondary brain injury. Recent improvements in quantitative assessments of metabolism, oxygenation, and subtle examination changes may potentially allow for more targeted, rational approaches beyond simple intracranial pressure (ICP)-based management. The authors present a case in which multimodality monitoring assisted in decision-making for decompressive craniectomy. OBSERVATIONS This patient sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…TBI treatment based on MMM-derived optimal cerebral perfusion has demonstrated improved clinical outcomes, especially in older patients who may have reduced autoregulatory capacity [ 114 ]. PRx allows for real-time measurement of cerebrovascular autoregulation [ 121 ] and may help to predict the need for surgical intervention in severe TBI [ 112 , 122 , 123 ]. Measurement of brain oxygenation parameters, such as P bt O 2 , allows for rapid implementation of therapeutic interventions to correct cerebral hypoxia [ 109 , 121 ], and measurement of P bt O 2 and ICP in the BOOST-II trial was suggested to improve secondary injury after TBI demonstrating the potential effect of such early interventions [ 116 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TBI treatment based on MMM-derived optimal cerebral perfusion has demonstrated improved clinical outcomes, especially in older patients who may have reduced autoregulatory capacity [ 114 ]. PRx allows for real-time measurement of cerebrovascular autoregulation [ 121 ] and may help to predict the need for surgical intervention in severe TBI [ 112 , 122 , 123 ]. Measurement of brain oxygenation parameters, such as P bt O 2 , allows for rapid implementation of therapeutic interventions to correct cerebral hypoxia [ 109 , 121 ], and measurement of P bt O 2 and ICP in the BOOST-II trial was suggested to improve secondary injury after TBI demonstrating the potential effect of such early interventions [ 116 ].…”
Section: Resultsmentioning
confidence: 99%
“…Invasive MMM is generally considered safe [ 210 ], however, noninvasive approaches to MMM could expand its use to the mTBI population. Noninvasive measurements of ICP, including optic nerve sheath diameter, have been shown to correlate with invasive ICP measurement techniques and help guide surgical management of TBI [ 112 , 211 ], and thus may allow MMM to guide treatment in mTBI without insertion of invasive monitoring devices. However, noninvasive techniques have significant variation in inter-user reliability [ 212 ], and have not demonstrated an ability to monitor changes in ICP over time [ 213 ], which significantly limits their ability to guide treatment.…”
Section: Discussionmentioning
confidence: 99%
“…TBI treatment based on MMM-derived optimal cerebral perfusion has demonstrated improved clinical outcomes, especially in older patients who may have reduced autoregulatory capacity [81]. PRx allows for real-time measurement of cerebrovascular autoregulation [82] and may help to predict the need for surgical intervention in severe TBI [83][84][85]. Measurement of brain oxygenation parameters such as PbtO2 allows for rapid implementation of theraputic interventions to correct cerebral hypoxia [82,86], and measurement of PbtO2 and ICP in the BOOST-II trial was suggested to improve secondary injury after TBI demonstrating the potential effect of such early interventions [87].…”
Section: Multimodal Neuromonitoringmentioning
confidence: 99%
“…Invasive MMM is generally considered safe [175], however noninvasive approaches to MMM could expand its use to the mTBI population. Noninvasive measurements of ICP including optic nerve sheath diameter have been shown to correlate with invasive ICP measurement techniques and help guide surgical management of TBI [83,176], and thus may allow MMM to guide treatment in mTBI without insertion of invasive monitoring devices. However noninvasive techniques have significant variation in inter-user reliability [177], and have not desmonstrated an ability to monitor changes in ICP over time [178], which significantly limits their ability to guide treatment.…”
Section: Imaging-and Neuromonitoring-guided Treatmentmentioning
confidence: 99%